Surveillance of Healthcare-Associated Bloodstream and Urinary Tract Infections in a National Level Network of Indian Hospitals. (October 2020) - Mathur, Purva; Malpiedi, Paul; Walia, Kamini; Malhotra, Rajesh; Srikantiah, Padmini; Katoch, Omika; Katyal, Sonal; Khurana, Surbhi; Misra, Mahesh Chandra; Gupta, Sunil; Kumar, Subodh; Sagar, Sushma; et al.
Abstract : Background: Healthcare-associated infections (HAIs) are a major global threat to patient safety. Systematic surveillance is crucial for understanding HAI rates and antimicrobial resistance trends and to guide infection prevention and control (IPC) activities based on local epidemiology. In India, no standardized national HAI surveillance system was in place before 2017. Methods: Public and private hospitals from across 21 states in India were recruited to participate in an HAI surveillance network. Baseline assessments followed by trainings ensured that basic microbiology and IPC implementation capacity existed at all sites. Standardized surveillance protocols for central-line–associated bloodstream infections (CLABSIs) and catheter-associated urinary tract infections (CAUTIs) were modified from the NHSN for the Indian context. IPC nurses were trained to implement surveillance protocols. Data were reported through a locally developed web portal. Standardized external data quality checks were performed to assure data quality. Results: Between May 2017 and April 2019, 109 ICUs from 37 hospitals (29 public and 8 private) enrolled in the network, of which 33 were teaching hospitals with >500 beds. The network recorded 679, 109 patient days, 212, 081 central-line days, and 387, 092 urinary catheter days. Overall, 4, 301 bloodstream infection (BSI) events and 1, 402 urinary tract infection (UTI) events were reported. The network CLABSI rate was 9.4 per 1, 000 central-line days and the CAUTI rate was 3.4 per 1, 000 catheter days. The central-line utilization ratio was 0.31 and the urinary catheter utilization ratio was 0.57. Moreover, 3, 542 (73%) of 4, 742 pathogens reported from BSIs and 868 (53%) of 1, 644 pathogens reported from UTIs were gram negative. Also, 1, 680 (26.3%) of all 6, 386 pathogens reported were Enterobacteriaceae. Of 1, 486 Enterobacteriaceae with complete antibiotic susceptibility testing data reported, 832 (57%) were carbapenem resistant. Of 951 Enterobacteriaceae subjected to colistin broth microdilution testing, 62 (7%) were colistin resistant. The surveillance platform identified 2 separate hospital-level HAI outbreaks; one caused by colistin-resistant K. pneumoniae and another due to Burkholderia cepacia . Phased expansion of surveillance to additional hospitals continues. Conclusions: HAI surveillance was successfully implemented across a national network of diverse hospitals using modified NHSN protocols. Surveillance data are being used to understand HAI burden and trends at the facility and national levels, to inform public policy, and to direct efforts to implement effective hospital IPC activities. This network approach to HAI surveillance may provide lessons to other countries or contexts with limited surveillance capacity. Funding: None Disclosures: None